Aligning Indonesia’s Energy-Market Competition Law with the Sustainable Development Goals: Pathways to a Just Energy Transition - Anisah, Siti; Heriyanto, Dodik Setiawan Nur (Prophetic Law Review, 2025)
Indonesia’s Sustainable Finance Roadmaps (2015-2019; 2021-2025) elevate renewable-energy investment to a national priority, yet the 2023 primary-energy mix is still dominated by coal (39.7 %) and petroleum (29.9 %), with new-and-renewable energy (NRE) at just 13.3 % far short of the 23 % statutory target for 2025. This article undertakes a doctrinal methodology to determine whether the country’s current legal architecture furnishes the pro-competitive conditions required to mobilise private capital toward NRE in harmony with the Roadmaps and Sustainable Development Goals 7, 13, and 16. The study systematically interprets (i) Law No. 30 of 2009 on Electricity, Law No. 22 of 2001 on Oil and Gas, and Law No. 21 of 2014 on Geothermal; (ii) implementing regulations and ministerial decrees on grid access, procurement, and feed-in tariffs; (iii) the Law No. 5 of 1999 and its 2023 implementing guidelines; and (iv) OJK Regulation No. 51/POJK.03/2017 on sustainable-finance disclosure. Statutory provisions are examined for hierarchical consistency, internal coherence, and conformity with Article 33(3) of the 1945 Constitution and Indonesia’s treaty obligations under the Paris Agreement. Doctrinal scrutiny reveals three normative defects: (1) the electricity law’s exclusive procurement mandate enables PLN’s de facto monopsony, contravening the non-discrimination principle in the Competition Law; (2) opaque tariff-setting regulations conflict with transparency duties embedded in the sustainable-finance framework; and (3) sectoral licensing rules omit explicit alignment with OJK’s green-taxonomy criteria, undermining legal certainty for renewable-energy sponsors. The article recommends statutory amendments to embed open-access grid clauses, mandate competitive tendering consistent with fair-competition norms, and cross-reference green-taxonomy thresholds in energy licences. These reforms would synchronise Indonesia’s competition regime with its sustainable-finance objectives and supply the legal certainty essential for a just energy transition.